Study on the Structure of GaN films deposited on MoS2/Sapphire via Plasma-Assisted Molecular Beam Epitaxy - Iwan Susanto; Chi-Yu Tsai; Nurzal Nurzal; M Zalu Purnomo; Ing-Song Yu (Recent in Engineering Science and Technology, 2023)
The gallium nitride (GaN) films were grown on molybdenum disulfide (MoS2) layers via plasma-assisted molecular beam epitaxy (PA-MBE). The heterostructures of the GaN film were studied using reflection high-energy electron diffraction (RHEED) and HR-XRD. The heterostructures of GaN/MoS2/sapphire were revealed through cross-sectional transmission electron microscopy (TEM). The surface texture of the GaN films was analyzed using FE-SEM. Single-crystal heterostructure GaN films can be obtained on 2D MoS2/c-sapphire. The RHEED demonstrated spot patterns with high intensity showing the single crystal structure constructed in the GaN films. The GaN films on the surface exhibited a hexagonal structure. TEM images taken perpendicular to the surface revealed that, even after 60 minutes of epitaxial growth, the thickness of the GaN films remained consistent at approximately 4 nm. However, the 2D MoS2 layer was not observable in the images due to harm incurred during heteroepitaxial growth. Based on the surface structure, it was found that GaN films were successfully grown on the MoS2 layers using the PA-MBE system.